THE IMPORTANCE OF EDUCATION IN THE PENITENTIARY SYSTEM AND ITS RESIGNIFICATION IN RESOCIALIZATION - Feitosa Aguiar, Anarleth (Revista Gênero e Interdisciplinaridade, 2022)
This article discusses some aspects about the importance of education and its resignification in socialization in the Penitentiary system. It is noticed that there is no concern for most citizens with the re-socialization of prisoners, which is why this research seeks to demonstrate the possibility of changing the behavior of that human being who is vulnerable when he is deprived of his freedom and at the time of return to society, building some public policy projects, specifically in the area of education, which seek ways to reduce the recurrence rate and, consequently, to prevent crime inside and outside the prison. Therefore, we seek to understand how this reinsertion takes place in the face of prisons in relation to the education processes, addressing the aspects of integration of the inmates, in which he believes that there is a policy of re-socialization for the detainees, including them in the face of the events that are occurring and outlining listening and debate methods, where everyone deserves the free will to express their opinions.